Patterns of Vascular Events and Risk Factors of Stroke- A Retrospective Study in a Tertiary Care Hospital of Bangladesh (Medicine Today, 2015)
Although stroke can affect any age but overall its incidence increases with advanced age. A number of risk factors affect stroke incidence. Here, we have tried to focus on relation of age and sex with stroke incidence as well as identification of modifiable risk factors, both of which bears important implications both patients and physicians. This retrospective study was undertaken by analyzing previous records of patients admitted in medicine ward of Shahabuddin Medical College and Hospital Dhaka, Bangladesh, from June 2013 to December 2014. Patients with stroke confirmed by CT/MRI scan were included in the study. Patients age, sex, risk factors including smoking, diabetes mellitus, hypertension and dyslipidemia were recorded from the history sheets and attached investigation slips. A total of 64 patients diagnosed as having stroke by CT/MRI scan were included. Overall male and female ratio was 1.2:1. In the study cerebral infraction, intra cerebral haemorrhage and subarachnoid haemorrhage were found in 71.87%, 20.31%, and 7.81%patients respectively. Most patients were between 40-79 years with male predominance but above 80 years female patients more than male. Among the stroke patients hypertension was found in 60.93% patients followed by smoking 48.43% dyslipidemia 40.38% and diabetes mellitus 37.93%. Stroke can be regarded as a preventable disease to large extent. Quitting smoking, detecting and treating most of the modifiable risk factors can go a long way to protect the community against stroke.Medicine Today 2015 Vol.27(1): 12-14